International-Mindedness: Deviations, Incongruities and Other Challenges Facing the Concept. (August 2018) - Savva, Maria; Stanfield, Dave
This article examines the developing discourse of international-mindedness and the problematic nature of its theoretical foundation alongside its actual manifestation in international school settings. In particular, it explores the discord between international-mindedness as a benevolent form of character development compared to international-mindedness as an opportunistic form of social and global mobility. Against this competing backdrop, the article also looks to identify distinct features that differentiate the concept of international-mindedness from other more established ideologies, including those related to interculturalism, multiculturalism and cosmopolitanism. The assumption that international-mindedness is perpetually situated within a moral code of conduct is challenged and analyzed critically, along with implications for schools.